TRADISI MALAMANG DALAM PROSESI ACARA MAULID NABI SAW DI PARIAMAN - Siska Aprisia; Susas Rita Loravianti; Febri Yulika (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT Malamang rite is an artwork inspired from the cultural phenomenon in Pariaman. That cultural phenomenon is the ritual of prophet Muhammad’s mauled ceremony, that is always conducted routinely particularly in surau. The sequence of that ritual consists of salawaik dulang, badikiah, baretong, arak-arakan (procession), and bajambua. One of traditions that cannot be forgotten is malamang. The phenomenon occurred in Pariaman society is then processed into art creative concept that uses parts of that ritual symbolically. Salawaik dulang, badikiah, baretong, arak-arakan (procession), and bajambua become the basis of creation by taking only the certain parts. From that art creative concept, it’s then born the dance of malamang rite in the form of the performance of Indonesian modern dance. Meanings resulted from the dance performance of this malamang rite comprise of several things namely: (1) social status; (2) self-respect; (3) people’s economy; and (4) inner conflict. All those meanings are present symbolically or directly in the artwork.